Streamlining Technical Measured on Medical Products to Combat COVID-19 - Jensen, Michael Friis; Sela, Shane; Brenton, Paul; Keyser, John (World Bank, Washington, DC, 2020)
The urgency of effective responses to the COVID-19 pandemic and the reliance of many low-income countries on imports of medical products, requires new approaches to regulation of these products. The challenge will be particularly acute for the new tests to identify infection, drugs to alleviate symptoms and machines to aid recovery as well as vaccines that are all expected to be developed in the coming months. Increased transparency, information sharing and greater cooperation among agencies responsible for the approval and inspection of medical goods around the world can help officials in low-income countries implement their mandate more effectively while maximizing efficient access to these commodities. Responsible agencies should focus on implementing technical regulations to protect health and safety, including interception of counterfeit and substandard products, and avoid wasting resources and creating delays by maintaining procedural practices that may be better addressed through alternative risk management strategies or seeking to regulate quality issues, which are best left to the market. Where there is a need to rapidly approve, test and inspect new goods or varieties that have not previously been imported, such as new equipment and medicines, the adoption of mutual recognition and/or equivalence can provide effective mechanisms to avoid regulatory delays while maintaining high levels of safety.